Resistance for the right to the city: The case of housing cooperativism in El Salvador. - Quiñónez Portillo, Natalia Beatriz; Rivera García, Sofía Beatriz (Revista: Módulo Arquitectura CUC)
The Historic Center of San Salvador (CHSS), located at the heart of El Salvador's capital city, has been historically shaped by conflicts over land, public spaces, housing and other fundamental services for the reproduction of life. The present article aims to shed a light on the role played by the Center's inhabitants in their struggle for adequate housing, as an example of how people can tilt the power balance to their favor by organizing, in cooperatives specifically, in cities as unevenly developed as Latin American. Cooperative members inhabiting the city in highly precarious conditions have claimed back, in a context apparently in favor of certain gentrifying trends, their right to be part of urban transformations. In order to do so, they have proposed that collectivization of land tenure and democratic decision-making at the cooperative assemblies remain their non-negotiable principles throughout the process. Although the central government has faced several challenges in their attempt of assimilating and supporting the proposals coming from the housing cooperatives, joint coordination has paid off. To share a common political platform among government bodies and the inhabitants, precisely at the level of policy design and implementation, has allowed cooperatives to transform into potential opponents of those who extract wealth from a reduced, informal and speculative market of land and housing in the area. Results to this day constitute and unprecedented success towards conceptualizing adequate housing as a human right, not a commodity. It is with this purpose that housing cooperatives from the CHSS offer their own stories of resistance.